Diversity of phytoplankton community in Gold Coast ornamental lake, Pantai Indah Kapuk-Jakarta: Diversitas Komunitas Fitoplankton Di Danau Hias Gold Coast, Pantai Indah Kapuk-Jakarta - Bambang Widigdo; Niken TM Pratiwi; Inna Puspa Ayu; Amelia Fitriani (Tropical Fisheries Management Journal, 2020)
The Gold Coast ornamental lake at Pantai Indah Kapuk, Jakarta is artificial, shallow and not too wide. It receives runoff from residential drainage channels, that affects the trophic states of the waters and the phytoplankton that live in it. This study aims to analyze the diversity of phytoplankton communities temporally related to trophic states in these waters. Sampling was carried out monthly for one year on the physical and chemical parameters of the waters and phytoplankton. Furthermore, the analysis of community structure and diversity of, a, b, and g, as well as determining the level of trophic states using the Chlorophyceae index and Cyanophyceae index. During the observation, four classes of phytoplankton were obtained, Chlorophyceae, Bacillariophyceae, Cyanophyceae, and Euglenophyceae which in total consisted of 41 species (g), a1-12 totaling 20-28 species, and b which were relatively small. The value of diversity index (H ') is low, the evenness (E) is moderate, and the dominance (C) is low. The values ​​of the two trophic states indices indicated that the waters were in a eutrophic condition during the observation. In general, it can be concluded that the conditions of the waters were always eutrophic for one year, the diversity of phytoplankton is relatively low and did not show significant changes in species between observations.